Cellular signaling impacts upon GABAergic cortical interneuron development - Pai, Emily Ling-Lin; Stafford, April M.; Vogt, Daniel (Frontiers in Neuroscience, 2023)
The development and maturation of cortical GABAergic interneurons has been extensively studied, with much focus on nuclear regulation via transcription factors. While these seminal events are critical for the establishment of interneuron developmental milestones, recent studies on cellular signaling cascades have begun to elucidate some potential contributions of cell signaling during development. Here, we review studies underlying three broad signaling families, mTOR, MAPK, and Wnt/beta-catenin in cortical interneuron development. Notably, each pathway harbors signaling factors that regulate a breadth of interneuron developmental milestones and properties. Together, these events may work in conjunction with transcriptional mechanisms and other events to direct the complex diversity that emerges during cortical interneuron development and maturation.